Inses Digital dan Budaya Narsistik: Krisis Teologi Tubuh dalam Gereja Kontemporer - Simajuntak, Markus A. (Sekolah Tinggi Teologi Torsina Surakarta, 2025)
This study examines the crisis of body theology in the contemporary church resulting from digital incest phenomena and narcissistic digital culture through an interdisciplinary approach. By integrating exegetical analysis of Leviticus 18 and 1 Corinthians 6:18-20, Jean M. Twenge's cultural psychology perspective, and empirical data from KPAI (2025) and Barna Group (2024), this research reveals threats to bodily sanctity extending beyond the physical realm. Empirical findings demonstrate significant involvement in online incest content consumption and a strong correlation between social media usage and body image obsession that objectifies the body as a virtual commodity. Exegetical analysis affirms incest prohibition as a covenantal community identity marker, while the body is understood as the temple of the Holy Spirit that must not be commodified. Holistic pastoral interventions are effective in increasing youth participation and reducing the risk of deviance. Research implications demand integrated reform: liturgy affirming bodily sanctity, an empirically grounded body-theology curriculum, and empathetic, adaptive church leadership. The church must respond to digital dynamics through robust exegesis, empirical monitoring, and contextual pastoral intervention to restore the integrity of body theology as the foundation of Christian identity. Abstrak Penelitian ini mengkaji krisis teologi tubuh dalam gereja kontemporer akibat fenomena digital incest dan budaya narsistik digital melalui pendekatan interdisipliner. Dengan mengintegrasikan analisis eksegetis Imamat 18 dan 1 Korintus 6:18–20, perspektif psikologi budaya Jean M. Twenge, serta data empiris KPAI (2025) dan Barna Group (2024), penelitian ini mengungkap ancaman terhadap kekudusan tubuh yang melampaui ranah fisik. Temuan empiris menunjukkan keterlibatan signifikan dalam konsumsi konten inses daring serta korelasi kuat antara penggunaan media sosial dan obsesi body image yang mengobjektifikasi tubuh sebagai komoditas virtual. Analisis eksegetis menegaskan larangan inses sebagai penanda identitas komunitas perjanjian, sementara tubuh dipahami sebagai bait Roh Kudus yang tak boleh dikomodifikasi. Intervensi pastoral holistik terbukti efektif meningkatkan partisipasi pemuda dan mengurangi risiko penyimpangan. Implikasi penelitian menuntut reformasi terintegrasi: liturgi yang menegaskan kekudusan tubuh, kurikulum pendidikan teologi tubuh berbasis data empiris, dan kepemimpinan gereja yang empatik-adaptif. Gereja perlu merespons dinamika digital melalui eksegesis kokoh, pemantauan empiris, dan intervensi pastoral kontekstual untuk memulihkan integritas teologi tubuh sebagai fondasi identitas kristiani.